Disorganization of claudin‐11 and dysfunction of the blood‐testis barrier during puberty in a cryptorchid rat model. (13th April 2020) - Kato, Taiki; Mizuno, Kentaro; Nishio, Hidenori; Moritoki, Yoshinobu; Kamisawa, Hideyuki; Kurokawa, Satoshi; Nakane, Akihiro; Maruyama, Tetsuji; Ando, Ryosuke; Hayashi, Yutaro; Yasui, Takahiro
Abstract: Background: Cryptorchidism is known to impair spermatogenesis. The blood‐testis barrier (BTB) becomes defined in seminiferous tubules around puberty and provides a suitable environment for germ cells. Little is known about the BTB in undescended testes (UDT). Objectives: To determine the role of BTB during puberty in UDT using a non‐surgical cryptorchid rat model. Material and Methods: Unilateral cryptorchid male rats were intraperitoneally injected with non‐steroidal antiandrogen during intrauterine development; the testes were harvested at 4, 5, and 6 weeks after birth. Testicular histology, expression levels of the BTB proteins (claudin‐11, occludin, zonula occludens‐1), and apoptotic cells were evaluated by immunohistochemistry, Western blotting, and TUNEL assay. The functionality of the BTB was investigated by electron microscopy using the lanthanum tracer method. Results: The testicular histology of undescended testes 6 weeks after birth showed maturation arrest at the spermatocyte level. The BTB protein distributions were altered in the UDT, with a noticeable difference in claudin‐11(CLDN11) localization from 4 to 5 weeks after birth between control and UDT samples. BTB protein levels were similar. More apoptotic germ cells were detected in the adluminal compartment of tubules in the UDT than in the control testes. Electron microscopy showed that the lanthanum tracer was limited to the BTB of control testes, whereas it penetrated the BTB of UDT. Discussion: Here, loss of normal BTB function and impaired spermatogenesis were observed in UDT during puberty. CLDN11 is a pivotal tight junction protein belonging to the BTB. Tight junctions are considered as essential for normal spermatogenesis, and abnormal CLDN11 organization may cause UDT‐associated male infertility. Conclusion: CLDN11 disorganization within the BTB may cause spermatogenic impairment, possibly by limiting the BTB function.